Original papersNeurogenic markers of the inflammatory process in atopic dermatitis: relation to the severity and pruritus - Teresiak-Mikołajczak, Ewa; Czarnecka-Operacz, Magdalena; Jenerowicz, Dorota; Silny, Wojciech (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Introduction : Atopic dermatitis (AD) is a chronic and relapsing inflammatory skin disease, characterized by eczematous skin lesions and intensive pruritus. Recent studies have shed light on the role of the nervous system in the pathogenesis of AD. It can influence the course of the disease through an altered pattern of cutaneous innervation and abnormal expression of neuropeptides in the lesional skin. Aim : The aim of the study was to evaluate plasma concentrations of the nerve growth factor (NGF), substance P (SP) and vasoactive intestinal peptide (VIP) in AD patients in comparison to two control groups (healthy volunteers and patients suffering from psoriasis). Correlations between plasma levels of evaluated parameters, severity of the disease and selected clinical parameters (skin prick tests, total and antigen specific IgE levels) were also analysed. Material and methods: Seventy-five patients with AD, 40 patients with psoriasis and 40 healthy volunteers were included into the study. Patients with AD included 52 persons suffering from an extrinsic and 23 from an intrinsic type of the disease. The severity of skin lesions was assessed with SCORAD index. Pruritus was evaluated on the basis of the questionnaire assessing the extent, frequency and intensity of pruritus. Commercial enzyme-linked immunosorbent assays (SP, NGF: R&D Systems; and VIP: Phoenix Pharmaceuticals) were used to assess the neuropeptide and NGF plasma levels. Results: Nerve growth factor and VIP plasma concentrations were significantly higher in AD patients compared to psoriatic patients and healthy subjects. Substance P plasma concentrations were elevated in the extrinsic type of AD and psoriasis comparing to healthy volunteers. There were no statistically significant differences in NGF, SP and VIP plasma concentrations between the extrinsic and intrinsic type of AD. There was also no correlation between plasma levels of evaluated parameters (NGF, SP, VIP) and SCORAD index in both types of AD. However, plasma SP concentration correlated with intensity of pruritus in AD patients. Plasma VIP concentrations correlated with intensity of pruritus in the intrinsic type of AD and with IgE-mediated sensitization to moulds in the extrinsic type of disease. Conclusions : Our findings confirm that NGF and VIP play a prominent role in atopic inflammatory reactions and may serve as good alternative biomarkers of AD. The results of this study also suggest a similar important role of neuroimmune interactions in both variants of AD. Increased SP plasma concentrations in both AD and psoriasis point to its possible role in modulating immune-mediated inflammation in different chronic inflammatory skin diseases. Moreover, SP and VIP seem to influence the course of AD by increasing pruritus, whereas an elevated plasma VIP level in AD patients may be related to a risk of developing IgE-mediated sensitization to certain airborne allergens.